The Correlation Between Workload And Ergonomic Position With The Incidence Of Low Back Pain In Nurses At Pringsewu Regional Public Hospital - Novita Putri Hardiyati; Rizki Yeni Wulandari; Yunina Elasari; Ardinata Ardinata (INDOGENIUS, 2026)
Background & Objective: To determine the "Relationship Correlation Workload And Ergonomic Position With The Incidence Of Low Back Pain In Nurses At Pringsewu Regional Public Hospital". Method: The study used a quantitative method with a descriptive correlational design and a cross-sectional approach. The study population was all nurses in the inpatient ward. A sample of 62 respondents who met the inclusion and exclusion criteria were selected using the Proportionate Stratified Random Sampling technique. The research instruments used were the Workload questionnaire, the Ergonomic Position questionnaire, and the Quebec Back Pain Disability Scale (QBPDS). Data analysis was performed using the Gamma test. Result: The results of the study showed a significant relationship between workload and the incidence of low back pain (p = 0.001). There was also a significant relationship between ergonomic position and the incidence of low back pain (p = 0.001). Conclusion: It was concluded that workload and ergonomic position can influence the incidence of low back pain in nurses.